In vitro inhibitory effects of kaempferitrin on human liver cytochrome P450 enzymes - Ning Zhang (Pharmaceutical Biology, 2019)
Context: Kaempferitrinis (KF) is a bioactive flavonoid and possesses numerous pharmacological activities. However, whether KF affects the activity of human liver cytochrome P450 (CYP) enzymes remains unclear. Objective: This study investigates the effects of KF on eight major CYP isoforms in human liver microsomes (HLMs). Materials and methods: In vitro, HLMs were used to investigate the inhibitory effects of KF (100 μM) on the eight human liver CYP isoforms (i.e., 1A2, 3A4, 2A6, 2E1, 2D6, 2C9, 2C19, and 2C8), and corresponding probe substrates were used. Enzyme kinetic studies (0–50 μM of KF) were conducted to determine the inhibition mode of KF on CYP enzymes. Results: The results showed that KF inhibited the activity of CYP1A2, 3A4, and 2C9, with IC50 values of 20.56, 13.87, and 14.62 μM, respectively, but that other CYP isoforms were not affected. Enzyme kinetic studies showed that KF was not only a noncompetitive inhibitor of CYP3A4, but also a competitive inhibitor of CYP1A2 and 2C9, with Ki values of 7.11, 10.24, and 7.58 μM, respectively. In addition, KF is a time-dependent inhibitor for CYP3A4 with KI/Kinact value of 10.85/0.036 min/μM. Discussion: The in vitro studies of KF with CYP isoforms indicate that KF has the potential to cause pharmacokinetic drug interactions with other co-administered drugs metabolized by CYP1A2, 3A4, and 2C9. Conclusion: It is recommended that KF should not be used with other drugs metabolized by CYP1A2, 3A4, and 2C9. Further clinical studies are needed to evaluate the significance of this interaction.